2017
DOI: 10.1186/s12951-017-0284-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica nanoparticle exposure on mitochondrial function during neuronal differentiation

Abstract: BackgroundNanomedicine offers a promising tool for therapies of brain diseases, but potential effects on neuronal health and neuronal differentiation need to be investigated to assess potential risks. The aim of this study was to investigate effects of silica-indocyanine green/poly (ε-caprolactone) nanoparticles (PCL-NPs) engineered for laser tissue soldering in the brain before and during differentiation of SH-SY5Y cells. Considering adaptations in mitochondrial homeostasis during neuronal differentiation, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(95 reference statements)
2
23
0
Order By: Relevance
“…In addition, the fluorescence signal avoided the intrinsic background interference relatively, achieving the precision, accuracy, and selectivity of the detection [ 123 , 124 ]. Similarly, Ducray et al prepared ICG-encapsulated silica-PCL nanocomposites for laser tissue soldering, in which the exposure of ICG-encapsulated nanoparticles had significantly affected the mitochondrial function [ 125 ]. In another study, Park et al fabricated ICG sheath incorporated PCL fibers, which exhibited excellent NIR absorption efficiency, acceleration of the ICG release, and the substantial enhancement of the anticancer activity in conjunction with the hyperthermia effect [ 126 ].…”
Section: Icg-encapsulated Polymeric Compositesmentioning
confidence: 99%
“…In addition, the fluorescence signal avoided the intrinsic background interference relatively, achieving the precision, accuracy, and selectivity of the detection [ 123 , 124 ]. Similarly, Ducray et al prepared ICG-encapsulated silica-PCL nanocomposites for laser tissue soldering, in which the exposure of ICG-encapsulated nanoparticles had significantly affected the mitochondrial function [ 125 ]. In another study, Park et al fabricated ICG sheath incorporated PCL fibers, which exhibited excellent NIR absorption efficiency, acceleration of the ICG release, and the substantial enhancement of the anticancer activity in conjunction with the hyperthermia effect [ 126 ].…”
Section: Icg-encapsulated Polymeric Compositesmentioning
confidence: 99%
“…11 In another study, it was reported that silica-indocyanine green/poly (ε-caprolactone) nanoparticles caused no neuronal differentiation because of mitochondrial damage. 95 We have summarized other nanoparticles that are having inhibitory and cytotoxic effects on neurons, in tabular forms. For example, inhibitory and cytotoxic effects on neurons studied in in vitro models are shown in Table 2, whereas inhibitory and cytotoxic effects studied in animal models are shown in Table 3.…”
Section: Inhibitory Effect Of Nanoparticles On Neuronal Cellsmentioning
confidence: 99%
“…[54]. Damage of mitochondrial functions can be provoked directly, i.e., by physical interaction of the nanomaterials with the mitochondrial membrane, or indirectly, e.g., by inducing damages through interactions with cell membrane protein receptors [56][57][58][59]. It is known that DNA is a critical target of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal acidification was calculated as the mean of three ECAR measurement cycles after oligomycin injection. The OCR data were corrected for non-mitochondrial oxygen consumption under rotenone and antimycin A [59]. Two repetitions of the Seahorse experiments were performed for data quantitation.…”
Section: Mitochondrial Stress Analysismentioning
confidence: 99%